Gripopterygidae (Plecoptera) from Paranapiacaba mountains, southeastern Brazil - Bispo, Pitágoras da Conceição [UNESP]; Lecci, Lucas Silveira [UNESP] (Cambridge University Press, 2011)
In the present paper, adults of the family Gripopterygidae collected in Paranapiacaba mountains are analyzed, the new species are described and a key to species of this family from this area is presented. Twenty one species in four genera of Gripopterygidae are recorded in Paranapiacaba mountains, São Paulo State, Brazil. Gripopteryx comprises six species: Gripopteryx cancellata, Gripopteryx reticulata, Gripopteryx garbei, Gripopteryx coruja, Gripopteryx pinima and Gripopteryx flinti. Paragripopteryx is represented by eight species: Paragripopteryx klapaleki, Paragripopteryx anga, Paragripopteryx blanda, Paragripopteryx egena, Paragripopteryx hamata and three new species: Paragripopteryx intervalensis, Paragripopteryx kapilei and Paragripopteryx paranapiacabae. Tupiperla is represented by six species: Tupiperla gracilis, Tupiperla tessellata, Tupiperla eleonorae, Tupiperla umbya and two new species, Tupiperla amandae and Tupiperla froehlichi. Guaranyperla is represented by only one species: Guaranyperla guapiara.
Keywords: Stoneflies; aquatic insects; diversity; streams; mountains